2001
DOI: 10.1159/000056336
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Photochemoprotection by Green Tea: A Brief Review

Abstract: Alarmingly increasing incidences of skin cancer are being reported from many countries where the majority of the population is Caucasian. According to projected estimates by the American Cancer Society, approximately 1.3 million cases of basal-cell and squamous-cell cancers, grouped together as nonmelanoma skin cancers, are diagnosed annually in the USA alone. It is clear that excessive exposure of the skin to solar radiation, particularly the UVB component, is responsible for these cancers. It is also importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 19 publications
1
23
0
1
Order By: Relevance
“…[316][317][318][319][320] The individual potential of these compounds also varies in usage for development of cosmeceutical products. Green tea components have multiple skin care roles such as antiaging and prevention of UV-induced photoaging.…”
Section: Nanogreen Teamentioning
confidence: 99%
See 1 more Smart Citation
“…[316][317][318][319][320] The individual potential of these compounds also varies in usage for development of cosmeceutical products. Green tea components have multiple skin care roles such as antiaging and prevention of UV-induced photoaging.…”
Section: Nanogreen Teamentioning
confidence: 99%
“…Green tea components have multiple skin care roles such as antiaging and prevention of UV-induced photoaging. 316,[320][321][322][323] The bioactive compounds readily undergo functional group loss during the exposure to environmental conditions and decrease the stability of the compounds, which limits the application of these compounds in cosmeceutical products. Nanodelivery techniques enhance the bioavailability of these compounds in cosmeceutical products, thereby enhancing their usage in the novel development of green tea-based cosmeceuticals.…”
Section: Nanogreen Teamentioning
confidence: 99%
“…A number of mechanisms explaining tea's anti-cancer actions have been presented including results suggesting that the gallate structure of theaflavins is important for growth inhibition of tumor cell lines by these compounds . One of the most well known actions of tea-associated polyphenolic compounds is their potent antioxidant activity, which has been suggested to be important in alleviating cancer-associated oxidative stresses Benzie et al, 1999;Brown, 1999;Katiyar et al, 1999;Kondo et al, 1999;Lin et al, 1999;Weisburger, 1999b;Weisburger, 1999a;Chen et al, 2000a;Ichihashi et al, 2000;Johnson and Loo, 2000;Jovanovic and Simic, 2000;Katiyar, Ahmad et al, 2000;Langley-Evans, 2000;Liu et al, 2000;Shi et al, 2000;Trevisanato and Kim, 2000;Ahmad and Mukhtar, 2001;Katiyar et al, 2001a;Katiyar, Bergamo et al, 2001b;Katiyar and Elmets, 2001;Owuor and Kong, 2002;. Results of one recent study in which normal human epidermal keratinocytes (NHEK) were pretreated with EGCG prior to UVB exposure, indicated that EGCG inhibited UVBinduced hydrogen peroxide (H 2 O 2 ) production and H 2 O 2 -mediated phosphorylation of mitogen-activated protein kinase (MAPK) signaling pathways (Katiyar et al, 2001a).…”
Section: Possible Mechanisms For Anti-cancer Activities Of Teamentioning
confidence: 99%
“…Tea is one of the most popular beverages consumed in the world and has been demonstrated to have anti-cancer activity in animal models. Several very recent review articles have summarized research findings regarding the anti-carcinogenic effects of tea Fujiki, 1999;Gupta et al, 1999;Mukhtar and Ahmad, 1999;Weisburger 1999b;Katiyar et al, 2000;Kong et al, 2000;Lin and Liang 2000;Trevisanato and Kim, 2000;Wang, 2000;Yang et al, 2000a;Ahmad and Mukhtar, 2001;Dong et al, 2001;Katiyar et al, 2001b;Katiyar and Elmets, 2001;Wiseman et al, 2001;Gupta and Mukhtar, 2002;Guyton and Kensler, 2002;Le Marchand, 2002;Yang et al, 2002).…”
Section: Introduction and Scope Of The Reviewmentioning
confidence: 99%
“…본 연구에서는 탁월한 항산화 기 능 식물로 알려진 녹차, 어성초, 자소엽을 사용하여 항 산화 기능이 우수한 복합물질을 개발하고자 연구를 진행하였다. 녹차(Camellia sinensis)의 카테킨(catechin) 과 EGCG는 암 발생 예방, 항산화, 항염증효과가 있다 [12][13][14]. 어성초(Houttuynia cordata)는 삼백초과(Saururaceae) 다년생 초본 식물로서 methyl-n-nonylketon, decanoyl acetaldehyde, α-pinene, linalool, δ-limonen, camphene, quercitrin, quercetin, reynoutrin, isoquercitrin, hyperin 등 다양한 성분들을 함유하고 있으며 항산화, 항균, 항알러지, 면역력 증진 등의 효능이 우수한 것 으로 보고된 바 있다 [15][16][17][18][19][20].…”
unclassified